Revision of the family Heterolatzeliidae (Diplopoda, Chordeumatida) - Makarov, Slobodan E.; Ćurčić, Božidar P. M.; Tomić, Vladimir T.; Rađa, Tonći; Rađa, Biljana; Ćurčić, Srećko B.; Mitić, Bojan M.; Lučić, Luka R. (Zootaxa, 2011)
A new genus is established for a new diplopod species from Croatia: Massarilatzelia dugopoljica n. gen, n. sp., which is described, thoroughly illustrated, and diagnosed. Two subspecies of the genus Heterolatzelia Verhoeff, 1897, H. nivalis rupivaga Verhoeff, 1899, and H. nivalis absoloni Attems, 1951 are synonymized and attributed to H. nivalis Verhoeff, 1897. Analysis of postembryonic development showed that in the representatives of the family Heterolatzeliidae the type of anamorphosis is teloanamorphosis. A key to genera and species of the family is presented, as well as an account of their geographic distribution.